Actual aspects of medical use of woloski nut extracts (Juglans regia l.) and black walnut (Juglans nigra l.) (review) - Mozhaiev, Ivan (Annals of Mechnikov’s Institute, 2023)
Recently, in the development of local medicines for the treatment of wounds, the interest of researchers in the use of plant raw materials that have antimicrobial, anti-inflammatory and reparative properties does not disappear. It is known from literary sources that among the plant substances that can be used in the treatment of wound infection, walnut (Juglans regia L.) and black walnut (Juglans nigra L.) nut family – Juglandaceae. The medical use of walnut in medicine and cosmetology is found in all parts of this plant: fruits, green pericarp, leaves, bark of branches and roots. Walnut leaves were used in the form of infusions and decoctions in the treatment of purulent and fungal lesions of the skin, pulmonary and other forms of tuberculosis, diabetes mellitus, diseases of the mucous membrane of the mouth and throat, thrush, vitamin deficiency. Black walnut should not be confused with walnut. Although they belong to the same family, they have significant differences. For a long time, the medicinal properties of Juglans nigra remained unexplored. The beneficial properties and contraindications of black walnut largely depend on the composition of the kernels, as they are most often the basis of biologically active supplements. Ripe fruits contain eight fatty acids, up to 30 % protein and 7 % carbohydrates. Juglone found in nuts is of great importance for health. The substance has an antifungal, antiparasitic, antimicrobial effect, improves intestinal function, restores the mucous membrane. Juglone inhibits the activity of phosphatidylinositol-3-kinase, which indicates its anticarcinogenic properties, while the toxicity inherent to other cytostatics was not detected. Juglon has a wide range of antibacterial activity, both in relation to gram-positive microorganisms (Staphylococcus aureus, Streptococcus mutans), and in relation to gram-negative microorganisms (Escherichia coli, Pseudomonas aeruginosa), as well as to pathogenic yeast fungi (Candida albicans). The complex pathogenesis of the wound process necessitates the creation of fundamentally new drugs with multidirectional action. Under these circumstances, it is important to create multicomponent ointments containing antibacterial and anti-inflammatory substances, antioxidants, and local anesthetics. The antibacterial effect of juglone and its derivatives against oral pathogens Porphyromonas spp, Streptococcus mutans, Actinobacillus viscasus, S. sobrinus, S. salivarius has also been proven. The complex of pharmacological properties of juglone determines the effectiveness in the treatment of various skin diseases. Based on the above, the development of a new original combined medicinal product based on plant raw materials - extracts of black walnut or walnut, antiseptic miramistin and anesthetic lidocaine hydrochloride in the form of an antimicrobial ointment for the treatment of wounds and wound infection is expedient and promising. In the laboratory of antimicrobial agents of SI IMI NAMS studies on antimicrobial activity were conducted and high and moderate antimicrobial effect of extracts of walnut (Juglans regia L.) and black walnut (Juglans nigra L.) was established, the antibacterial effect of Porphyromonas spp, Streptococcus mutans, Actinobacillus viscasus, S. sobrinus, S. salivariu was proved. Conclusion. Based on the above, the development of a new original combined medicinal product based on plant raw materials - extracts of black walnut (Juglans nigra L.) and walnut (Juglans regia L.), antiseptic miramistin and anaesthetic lidocaine hydrochloride for injection. relevant and promising.